2012
DOI: 10.1590/s0100-40422012001000010
|View full text |Cite
|
Sign up to set email alerts
|

Hidroformilação do oleato de metila catalisada por complexos de ródio

Abstract: Recebido em 18/1/12; aceito em 20/6/12; publicado na web em 31/8/12HYDROFORMYLATION OF METHYL OLEATE CATALYZED BY RHODIUM COMPLEXES. In this work, we describe the hydroformylation of methyl oleate catalyzed by several rhodium complexes. Parameters including total pressure, phosphorous/ rhodium and CO/H 2 ratio, temperature and phosphorous ligands were scanned. Total conversion of the starting double bonds was achieved while maintaining excellent selectivity in aldehydes.Keywords: methyl oleate; hydroformylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…They achieved quantitative conversion along with a high selectivity toward the formation of aldehydes (80–91%) when an excess of PPh 3 (PPh 3 /Rh = 10) was applied under 40 bar of syngas pressure (CO/H 2 = 2:1) at 100 °C. The same authors reported that RhH­(CO)­(PPh 3 ) 3 gives rise to a similar catalytic performance . Notably, catalysts generated from RhCl 3 ·3H 2 O, [Rh­(OMe)­(cod)] 2 or Rh­(CO) 2 (acac) were inferior.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…They achieved quantitative conversion along with a high selectivity toward the formation of aldehydes (80–91%) when an excess of PPh 3 (PPh 3 /Rh = 10) was applied under 40 bar of syngas pressure (CO/H 2 = 2:1) at 100 °C. The same authors reported that RhH­(CO)­(PPh 3 ) 3 gives rise to a similar catalytic performance . Notably, catalysts generated from RhCl 3 ·3H 2 O, [Rh­(OMe)­(cod)] 2 or Rh­(CO) 2 (acac) were inferior.…”
Section: Introductionmentioning
confidence: 93%
“…The same authors reported that RhH(CO)(PPh 3 ) 3 gives rise to a similar catalytic performance. 18 Notably, catalysts generated from RhCl 3 •3H 2 O, [Rh(OMe)-(cod)] 2 or Rh(CO) 2 (acac) were inferior. Recently, Monflier and co-workers gave evidence that the hydroformylation of MO can be advantageously carried out in aqueous media with Rh-TPPTS [trisodium salt of 3,3′,3″-phosphinidynetris(benzenesulfonic acid] as catalyst and activated carbon as an additive.…”
Section: ■ Introductionmentioning
confidence: 99%